2021
DOI: 10.1111/cas.15001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of brain tumor recurrence using 11C‐methionine positron emission tomography after radiotherapy

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…[ 3 , 4 , 6 , 7 , 9 , 11 , 14 ] However, the high glucose utilization of the normal brain frequently complicates the identification of brain tumors. [ 3 , 6 , 8 , 11 , 15 ] On the other hand, due to the low uptake of amino acids in the brain, the contrast between tumors and normal brain is generally better visualized with amino acid scanning. [ 8 , 12 , 15 ] Although the degree of FDG uptake does not always reflect the grade or progression of primary brain tumors,[ 4 , 14 ] MET-PET is more efficient in delineating gliomas and in differentiating recurrence from radiation necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 3 , 4 , 6 , 7 , 9 , 11 , 14 ] However, the high glucose utilization of the normal brain frequently complicates the identification of brain tumors. [ 3 , 6 , 8 , 11 , 15 ] On the other hand, due to the low uptake of amino acids in the brain, the contrast between tumors and normal brain is generally better visualized with amino acid scanning. [ 8 , 12 , 15 ] Although the degree of FDG uptake does not always reflect the grade or progression of primary brain tumors,[ 4 , 14 ] MET-PET is more efficient in delineating gliomas and in differentiating recurrence from radiation necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 , 12 , 15 ] Although the degree of FDG uptake does not always reflect the grade or progression of primary brain tumors,[ 4 , 14 ] MET-PET is more efficient in delineating gliomas and in differentiating recurrence from radiation necrosis. [ 1 , 2 , 9 , 12 , 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to ceMR, BBB disruption is not a prerequisite for intratumoral localization of radiotracer (140,141). Compared to FDG, AA radiotracers exhibit lower background physiologic uptake in the cerebral cortex and are expected to better differentiate between recurrence and treatment effect (142). Evidence in the literature suggests that the most commonly used AA PET tracers including, 11 C-methionine (MET), O-(2-18 Ffluoroethyl)-L-tyrosine (FET), and 18 F-DOPA all demonstrate similar diagnostic performance (143).…”
Section: Amino Acid Pet Radiotracersmentioning
confidence: 99%
“…Deuschl et al performed 11 C-MET PET/MR and conventional MR on a cohort of 50 glioma patients and reported the sensitivities and specificities as 86% and 71% for conventional MRI, 97 and 74% for 11 C-MET PET, and 97 and 93% for hybrid 11 C-MET PET/MR (144). In a multicenter prospective trial comparing the diagnostic performance of 11 C-MET with 18 F-FDG in identifying recurrence, Yamaguchi et al found that the diagnostic accuracy of 11 C-MET-PET at 88% was superior to that of 18 F-FDG-PET at 70% and reported the sensitivities of 11 C-MET-PET and 18 F-FDG-PET as 97 and 48%, respectively (142). Deng et al conducted a meta-analysis of 17 articles and found that 11 C-MET PET and DSC-MRI had comparable sensitivities of 87 and 88% as well as specificities of 81 and 85%, respectively (145).…”
Section: Amino Acid Pet Radiotracersmentioning
confidence: 99%